PENENTU KEBIJAKAN DIVIDEN PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Prabulana, Rahadian Dopin; Saiful, Saiful; Suranta, Eddy (UNIB Press, 2017)
The dividend distribution policy is a difficult financial decision for management. The research objective was to examine the determinants of the Dividend Payout Ratio (DPR) in companies listed on the Indonesian stock exchange. The independent variables used in this study are Free Cash Flow (FCF), Debt Rate (LEVERAGE), Foreign Ownership Level (FOREIGN), Growth Rate (GROWTH), and Company Size (SIZE).The research sample was 62 non-financial companies listed on the Indonesia Stock Exchange using multiple regression analysis. This study is exposed to the problem of classical assumptions, namely data normality and cannot be resolved due to the limitations of the study sample. This study is also affected by the problem of heteroscedasticity so that the hypothesis testing uses weighted least square (WLS).The results showed evidence that FCF, Growth and Size have an effect on dividend payment policies and Leverage and Foreign have no effect on dividend payments. This study shows that investors who expect dividend payments can invest in companies that have a high FCF, large size and low growth, on the other hand, if investors expect a greater investment return, it can be obtained from Capital Gain. This research also shows that agency conflicts related to FCF can be resolved through dividend payments.